2020
DOI: 10.1101/2020.08.18.255455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of histone inheritance patterns in theDrosophilafemale germline

Abstract: Stem cells have the unique ability to undergo asymmetric division which produces two daughter cells that are genetically identical, but commit to different cell fates. The loss of this balanced asymmetric outcome can lead to many diseases, including cancer and tissue dystrophy. Understanding this tightly regulated process is crucial in developing methods to treat these abnormalities. Here, we report that produced from a Drosophila female germline stem cell asymmetric division, the two daughter cells differenti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…We found asymmetric inheritance of old H3 and H4 in Drosophila male GSCs ( Wooten et al., 2019 ; Tran et al., 2012 ; Wooten et al., 2020 ; Ranjan and Chen, 2022 ). In addition, we also reported global histone H3-H4 asymmetry in Drosophila ISCs ( Chen and Zion, 2020 ) and local histone H3-H4 asymmetry in Drosophila female GSCs ( Kahney et al., 2020 ) and induced mouse embryonic stem cells (mESCs) ( Ma et al., 2020 ). These observations indicated that different systems regulate epigenome inheritance during ACD differently; it can be global or local at specific gene loci.…”
Section: Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…We found asymmetric inheritance of old H3 and H4 in Drosophila male GSCs ( Wooten et al., 2019 ; Tran et al., 2012 ; Wooten et al., 2020 ; Ranjan and Chen, 2022 ). In addition, we also reported global histone H3-H4 asymmetry in Drosophila ISCs ( Chen and Zion, 2020 ) and local histone H3-H4 asymmetry in Drosophila female GSCs ( Kahney et al., 2020 ) and induced mouse embryonic stem cells (mESCs) ( Ma et al., 2020 ). These observations indicated that different systems regulate epigenome inheritance during ACD differently; it can be global or local at specific gene loci.…”
Section: Limitationsmentioning
confidence: 84%
“…In this protocol, we use dual-color fluorescence tagged histones (e.g., H3, H4, and H2A) to track old versus new histone distribution and inheritance patterns in mitosis. Histones H3 and H4 show a global asymmetric inheritance in Drosophila male GSCs [ Figures 2 C and 2D ( Tran et al., 2012 ; Wooten et al., 2019 )] and intestinal stem cells (ISCs) ( Chen and Zion, 2020 ), whereas there is a local asymmetry in Drosophila female GSCs ( Kahney et al., 2020 ) and mouse embryonic stem cells ( Ma et al., 2020 ). However, H2A shows an overall symmetric inheritance pattern in Drosophila male and female GSCs as well as ISCs.…”
Section: Expected Outcomesmentioning
confidence: 99%